Detector electrode introduced by mediastinoscopy for atrial triggered cardiac pacing. A follow-up of electrode function in 82 patients. Issue 11 (November 1977) - Carlene, E; Ericsson, M; Levander-Lindgren, M; Pehrsson, K
Abstract : An atrial detector electrode was introduced by mediastinoscopy in 82 patients requiring permanent cardiac pacing. There were no complications. An adequate P wave was recorded in 80 patients. During the following week, the P wave became ineffective in 5 patients; angina occurred in 2 and atrial arrhythmias in 2. Atrially triggered ventricular pacing established in 73 patients and was followed in 71 patients for a period of 1 to 113 months. In 17 cases, it had to be terminated because of an ineffective or unstable P wave, in 6 cases because of atrial arrhythmias, and in 4 cases because of advanced age and recurrent infections. The method is technically simple and place little stress on the patient.